OCT4 Represses Inflammation and Cell Injury During Orchitis by Regulating CIP2A Expression - Zeng, Ruifeng; Jin, Chengli; Zheng, Chuchu; Li, Shaoqi; Qian, Siyue; Pan, Jingsa; Wang, Lvhe; Zhao, Junfeng; Qin, Le (Frontiers in Cell and Developmental Biology, 2021)
Octamer-binding transcription factor 4 (OCT4) and cancerous inhibitor of protein phosphatase 2A (CIP2A) are upregulated in testicular cancer and cell lines. However, its contribution to orchitis (testicular inflammation) is unclear and was thus, investigated herein. Cell-based experiments on a lipopolysaccharide (LPS)-induced orchitis mouse model revealed robust inflammation, apoptotic cell death, and redox disorder in the Leydig (interstitial), Sertoli (supporting), and germ cells. Meanwhile, real-time quantitative PCR revealed low OCT4 and CIP2A levels in testicular tissue and LPS-stimulated cells. A gain-of-function study showed that OCT4 overexpression not only increased CIP2A expression but also repressed LPS-induced inflammation, apoptosis, and redox disorder in the aforementioned cells. Furthermore, the re-inhibition of CIP2A expression by TD-19 in OCT4-overexpressing cells counteracted the effects of OCT4 overexpression on inflammation, apoptosis, and redox equilibrium. In addition, our results indicated that the Keap1-Nrf2-HO-1 signaling pathway was mediated by OCT4 and CIP2A. These findings provide insights into the potential mechanism underlying OCT4- and CIP2A-mediated testicular inflammation.